1998
DOI: 10.1111/j.1528-1157.1998.tb01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Pseudoatrophy of the Brain and Mental Deterioration Associated with Valproate Treatment

Abstract: Summary:Purpose: To describe an 11-year-old girl with symptomatic localization-related epilepsy and normal intelligence who developed reversible mental deterioration and pseudoatrophic brain changes while receiving valproate (VPA).Methods; Assessment of mental function using Wechsler Intelligence Scale for Children-I11 (WISC) and Raven's Progressive Matrices (PM), EEG recordings while awake and asleep, and brain magnetic resonance imaging (MRI), were performed at the beginning of VPA therapy, after 2 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 11 publications
3
39
0
5
Order By: Relevance
“…For example, gray matter volume (cortical and subcortical) has been reported to be negatively correlated with disease duration in GGE,7, 10, 14, 24 although some studies did not find thalamic volume and disease duration to be correlated,3, 23 which may relate to the patient group selected, or to other factors such as seizure frequency or AED treatment. The effect of AED treatment is unclear: although reports of animal studies have indicated effects on brain development, there are only case reports available in humans that confirm these effects 13, 31, 32…”
Section: Discussionmentioning
confidence: 99%
“…For example, gray matter volume (cortical and subcortical) has been reported to be negatively correlated with disease duration in GGE,7, 10, 14, 24 although some studies did not find thalamic volume and disease duration to be correlated,3, 23 which may relate to the patient group selected, or to other factors such as seizure frequency or AED treatment. The effect of AED treatment is unclear: although reports of animal studies have indicated effects on brain development, there are only case reports available in humans that confirm these effects 13, 31, 32…”
Section: Discussionmentioning
confidence: 99%
“…Some examples are VPA-induced encephalopathy [99,120] and PHT-induced dyskinesia. [121] Other systems or organs can also be involved.…”
Section: Most Frequent Idiosyncratic Adverse Effects To Aedsmentioning
confidence: 99%
“…[96] Off-target pharmacology: These reactions occur when a drug interacts directly with a system other than that for which it is intended. [97] Examples include some unusual CNS adverse effects such as Parkinsonian symptoms [98] or cognitive deterioration [99] with VPA, and dyskinesia with FBM. [64] …”
Section: Idiosyncratic Adverse Effectsmentioning
confidence: 99%
“…37 These reports indicate that dementia may develop shortly after the introduction of the valproate, 36,37 or the dementia may have an insidious and progressive course that becomes obvious only after chronic treatment. 38 Both the encephalopathy observed on MRI scans and the cognitive changes remit within days of discontinuation of the medication.…”
Section: Valproatementioning
confidence: 99%